Teaching Narrative Writing Using Freaky Fables Game: An Experimentation - Rahmawati, Istiqomah Nur; Syafryadin, Syafryadin; Widiastuti, Rizki (English Education: Jurnal Tadris Bahasa Inggris, 2019)
This study is an experimentation of the idea of using game to teach narrative writing in one of private primary schools in Bandar Lampung. 21 students were grouped according to their class (6A & 6B) into experimental and control.  The two groups were given pretest and post-test.  The experimental group was taught narrative writing using game called Freaky Fables, the control group was taught using the conventional method.  The experimental group also responded to a questionnaire which sought their reactions to the use of game in teaching narrative writing.  Data collected were analyzed.  Results shown that the experimental group performed significantly better than the control group due to treatment (the use of Freaky Fables game to teach narrative writing).  Consequently, the experimental group and the teachers involved showed favorable disposition to the continuous use of the method.